Pelatihan Public Speaking Dengan Memanfaatkan Aplikasi Zoom Di Masa Pandemi Covid-19 - Asriyani Sagiyanto; Achmad Syahlani; Liliyana Liliyana; Ferrari Lancia (LPPM Universitas Bina Sarana Informatika, 2021)
One aspect that has changed due to the Covid-19 pandemic is the way humans communicate in public (public speaking). This impact was also felt by women who were members of the Fatayat NU (Nahdlatul Ulama) Ciledug organization. Fatayat NU is an Islamic women's organization which is one of the autonomous institutions within NU, which is religious, social and familial. The concept of Fatayat NU activities can be classified into three, namely in the field of regeneration and education, the field of da'wah or Islamic development, and the field of social society. The problems faced by Fatayat NU Ciledug, relating to public speaking are: (1) Lack of ability to appear and speak in public; and (2) Lack of public speaking skills, both face-to-face and online. The solutions offered to solve these problems are through community service activities, namely providing online training/workshops by utilizing the Zoom Meeting application to members of Fatayat NU Ciledug to provide tips and tricks regarding: (1) How to have the ability to appear and speak in public; and (2) Skills in public speaking both face-to-face and online. The implementation of this community service activity consists of 3 stages, namely; (1) The preparation stage, to identify problems, apply for permits to the Fatayat NU Ciledug management, and make preparations for the implementation of public speaking training; (2) the stage of implementing public speaking training; and (3) the evaluation stage, by providing evaluation test questions that must be done using Google Forms media, to find out how much the increase in knowledge, abilities, and skills of Fatayat NU Ciledug women regarding public speaking after participating in training activities.